The efficacy of ELISA commercial kits for the screening of equine infectious anemia virus infection = Eficacia de ensayos de ELISA comerciales para el screening de infección por el virus de la anemia infecciosa equina - Alvarez, Irene (2015)
The most used and reliable indicator of equine infectious anemia virus (EIAV) infection is the detection of its specific antibodies in horse serum. In the present study, the performance of two commercial ELISA tests for the detection of EIAV antibodies as well as the potential advantages of their use as an EIAV infection screening tool were evaluated in 302 horse serum samples. Both ELISA assays showed 100% diagnostic sensitivity, and 92.3–94.3% diagnostic specificity. Discordant results were analyzed by immunoblot. The results showed that both ELISA tests are very efficient at detecting EIAV infected animals, allowing to identify a higher number of positive horse cases. Thus, ELISA assays can be useful tools in EIA control and eradication.